THE CORRELATION AMONG THE FACTORS OF IMPLEMENTATION, THE SYSTEM DEVELOPMENT, AND THE RESULT OF PERFORMANCE MEASUREMENT SYSTEM: A Study Conducted in The Regency of Sumba Timur - Kuba Yowi, Linda Rambu (Journal of Indonesian Economy and Business, 2011)
This study is aimed to examine the relationship among factors determining the success or failure of the implementation of performance measurement systems with the development of performance measurement systems, performance accountability, and the use of performance information in the government institutions and to examine the impacts of the development of performance measurement systems on the performance accountability and the use of performance information.This research was carried out in the Local Government of East Sumba Regency. The research respondents were the government officers of Echelon II, III, and IV. The samples were selected using purposive sampling.509 questionnaires were distributed and 267 were used. Data were analyzed using Ordinary Least Square (OLS).This research finds that organization culture and resources have relationship with the development of performance measurement systems. In contrast, the limited informationsystems, difficulties in determining the performance metrics, management commitment, decision-making authority, and training do not have relationship with the development ofperformance measurement systems. The limited information systems, difficulties in determining the performance metrics and training do not have relationship with the performanceaccountability, but management commitment, decision-making authority, organization culture, and resources have relationship with the performance accountability. The difficulties in determining the performance metrics, decision-making authority, organization culture, and resources have relationship with the use of performance information, whereas the limited information systems, management commitment, and training do not have relationship with the use of performance information. Further, the development of performance measurement systems directly influences the performance accountability and the use of performance information and indirectly influences the use of performance information through the performance accountability.Keywords: performance measurement, performance accountability, performance information, local government